2D-ERT data measured in October 2022 in the Ahr floodplain at Mayschoß, Rhineland-Palatinate (Germany) - Marco Pohle; Matteo Bauckholt; Ulrike Werban (PANGAEA, 2025)
The Electrical Resistivity Tomography (ERT) data were acquired by using a PC controlled DC resistivity meter system (RESECS, GeoServe, Kiel, Germany) in October 2022. We measured a total of four transects with an electrode spacing 1 m. Transect 1 has a total length of 255 m, transect 2 a total length of 207 m, transect 3 a total length of 136 m and transect 4 a total length of 158 m. For all transects we applied a Wenner alpha and Dipole-Dipole configuration. The coordinates and the height of the electrodes were measured with a Differential-GPS (Leica GPS1200). Further information on the measurement setup and data structure can be found in the explanation of the specific ERT transects.
In: Pohle, M et al. (2025): Near surface geophysical data (Electromagnetic Induction and Electrical Resistivity Tomography) from the Ahr floodplain at Mayschoß, Germany [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974990